2019
DOI: 10.15789/1563-0625-2019-3-517-526
|View full text |Cite
|
Sign up to set email alerts
|

Features of Immune Response in Preterm Babies With Bronchopulmonary Displasia of Various Severity

Abstract: To evaluate the immunity indexes in the children who were born with bronchopulmonary dysplasia (BPD) of varying severity at very early delivery terms (22-27 weeks), dynamic examinations were performed in 35 infants: 17 children were with severe BPD; 18, with mild-severity and moderately severe BPD. The comparison group consisted of seven children born at 22-27 weeks of gestational age without signs of BPD. Relative numbers of lymphocyte subpopulations (CD3+, CD4+, CD8+, CD19+, CD16+CD56+, CD4+CD25+), and monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recent research demonstrated that premature infant with severe BPD was featured with decreased level of monocytes (CD64, HLA-DR) at 1 month of life. In addition, reduced expression of CD14 + CD64 + cells weas observed at 38-40 weeks after conception [32]. The proportion of B cells and CD4 cells (CD62L) was reduced in BPD infants [33].The activation and polarization of macrophages play a crucial role in the development of lung diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Recent research demonstrated that premature infant with severe BPD was featured with decreased level of monocytes (CD64, HLA-DR) at 1 month of life. In addition, reduced expression of CD14 + CD64 + cells weas observed at 38-40 weeks after conception [32]. The proportion of B cells and CD4 cells (CD62L) was reduced in BPD infants [33].The activation and polarization of macrophages play a crucial role in the development of lung diseases.…”
Section: Discussionmentioning
confidence: 96%